Korelasi Pengetahuan Dan Sikap Dengan Stigma Masyarakat Terhadap Orang Dengan Gangguan Jiwa - Fitriani, Dhia Diana; Wahyuni, Citra Putri; Rohmah, Ulfa Nur; Kiani, Safa Tiara; Kasumawati, Frida (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2025)
Background: The increasing prevalence of mental disorders continues to be accompanied by a high level of community stigma, which contributes to delayed help-seeking behavior, poor treatment adherence, and a heightened risk of relapse. This study aims to analyze the correlation between the level of knowledge and attitudes with community stigma toward individuals with mental disorders in Kampung Kadongdong RT 002/003, Pasir Nangka Village, Tigaraksa District, Tangerang Regency. Methods: This research employed a descriptive analytic design with a cross-sectional approach and involved all 61 heads of households as respondents selected through a total sampling method. Data were analyzed using Chi-Square test with a significance level of α = 0.05. Results: Nearly half of the respondents had a moderate level of knowledge (47.5%), a neutral attitude (41.0%), and a low level of stigma (41.0%). There was a significant correlation between the level of knowledge and stigma (p = 0.000), as well as between attitudes and stigma (p = 0.005). Conclusion: This study showed a significant relationship between public knowledge and attitudes toward stigma against people with mental disorders; therefore, enhancing mental health literacy through education and anti-stigma campaigns was considered necessary to promote better understanding and acceptance of individuals with mental illnessBackground: The increasing prevalence of mental disorders continues to be accompanied by a high level of community stigma, which contributes to delayed help-seeking behavior, poor treatment adherence, and a heightened risk of relapse. This study aims to analyze the correlation between the level of knowledge and attitudes with community stigma toward individuals with mental disorders in Kampung Kadongdong RT 002/003, Pasir Nangka Village, Tigaraksa District, Tangerang Regency. Methods: This research employed a descriptive analytic design with a cross-sectional approach and involved all 61 heads of households as respondents selected through a total sampling method. Data were analyzed using Chi-Square test with a significance level of α = 0.05. Results: Nearly half of the respondents had a moderate level of knowledge (47.5%), a neutral attitude (41.0%), and a low level of stigma (41.0%). There was a significant correlation between the level of knowledge and stigma (p = 0.000), as well as between attitudes and stigma (p = 0.005). Conclusion: This study showed a significant relationship between public knowledge and attitudes toward stigma against people with mental disorders; therefore, enhancing mental health literacy through education and anti-stigma campaigns was considered necessary to promote better understanding and acceptance of individuals with mental illness